The Impact of agricultural guaranteed purchase prices on stock market - Wang, Vey; Chen, Chia-Hui; Lee, Lung-Sheng (2010)
In developing countries, farmers are generally poor and easily hurt by frequent price fluctuations of their products, especially when unexpected excess supply leads to substantially reduced prices. Governments therefore often adopt the policy of guaranteed purchase prices to protect farmers from the damages caused by the supply shock.
In recent years, the link between domestic stock market and real economic performance has become stronger, and is generally true even for the developing countries. The 1997-1988 Asian financial crisis very well exemplifies this. This paper extends the theoretical schemes to Frankel (1986), Chen (1998) and Lai, Hu and Wang (1996) to set up a dynamic theoretical closed economic model, which covers the agricultural market, manufacturing market, money market and stock market. As far as the authors know, this may be the first research to explore the connection between the agricultural market and the stock market using dynamic theoretical model.
When the unexpected excess supply of an agricultural product drags the price toward the guaranteed purchase price set by the government, the government will purchase the excess supply as much as necessary in order to maintain the price equal to the predetermined guaranteed purchase price. Our model predicts that the price of agricultural products will eventually fall to the level of the government's guaranteed price and stock price will start to rise. This is probably because the decrease in the price of agricultural products from collapsing further. This in turn will maintain farmers' purchasing power for manufactured goods and the stock market will begin to rise.
Keywords: Stock market; Money market